Social Media Addiction and Life Satisfaction: The Mediating Effect of Self-Esteem in University Students - Giri, Priyanka; Shrestha, Anurag (DAV Research Journal, 2025)
This study examines the relationship between social media addiction, self-esteem, and life satisfaction among university students in Nepal. Specifically, it investigates whether self-esteem mediates the relationship between social media addiction and life satisfaction in the context of increasing digital dependency. A quantitative cross-sectional research design was employed. Data were collected from 150 university students in the Kathmandu Valley of Nepal using validated psychological scales – the Social Media Addiction Questionnaire, Rosenberg Self-Esteem Scale, and Satisfaction with Life Scale. Structural Equation Modeling using SmartPLS was used to test the direct and indirect relationships among the variables. The results showed that social media addiction had a significant positive effect on self-esteem, likewise self-esteem had a significant positive effect on life satisfaction. However, there was no significant direct effect of social media addiction on life satisfaction. Self-esteem was found to partially mediate the relationship between social media addiction and life satisfaction. The study shows that social media addiction does not directly influence life satisfaction but has an indirect positive effect through self-esteem. This finding highlights self-esteem as an important factor linking social media use with overall well-being. The findings suggest that social media addiction, when managed positively, can enhance self-esteem, likewise it improves life satisfaction among students. This indicates that interventions should prioritize strengthening self-esteem and promoting healthy patterns of social media use. The results also provide theoretical support for understanding how these variables interact within a collectivist cultural context. This is one of the few empirical studies in Nepal that investigates the psychological impacts of social media addiction on university students. It offers new insights into how self-esteem can act as a protective psychological mechanism in the digital age.